The Association Between the Rotator Cuff Status and the Severity and Recovery of Weakness in the Shoulder Abductor Strength in a Case of Proximal Type Cervical Spondylotic Amyotrophy. Issue 7 (September 2022) - Ishiwata, Sho; Iizuka, Yoichi; Shitara, Hitoshi; Mieda, Tokue; Takasawa, Eiji; Tsunoda, Daisuke; Kakuta, Yohei; Honda, Akira; Ito, Shunsuke; Inomata, Kazuhiro; Sasaki, Tsuyoshi; Hamano, Noritaka; et al.
Study Design: Case series study. Objective: We aimed to clarify the prevalence of rotator cuff tear (RCT), and the association between RCT and the severity and prognosis in patients with proximal type cervical spondylotic amyotrophy (CSA). Methods: We retrospectively analyzed 35 proximal type CSA patients who were treated conservatively. The following data was collected: age, rotator cuff status on MRI, manual muscle test (MMT) score of shoulder abductor and biceps brachii muscles both at the first visit and final follow-up. We investigated the prevalence of RCT and the association between the rotator cuff status, and the severity and recovery of upper extremity weakness in patients with proximal type CSA. Results: Of the 35 patients, 21 had an RCT on MRI, indicating that the prevalence of RCT in patients with proximal type CSA was 60%. An age-adjusted analysis showed that the presence of RCT was significantly associated with the MMT score of the shoulder abductor muscles both at the first visit and at the final follow-up. The presence of RCT was significantly associated with the recovery of the shoulder abductor muscles. The size of the RCT was negatively correlated with the MMT score of the shoulder abductor muscles at the final follow-up. The size of the RCT was independently correlated with the change of the MMT score of the shoulder abductor muscles. Conclusion: RCT was detected in >50% in patients with proximal type CSA, and the presence and severity of RCT can be used as prognostic factors for proximal type CSA patients who are treated conservatively.